Mudharabah and Musyarakah Financing in Indonesian Islamic Banking Practices: Is It Equity or Debt Financing? - Purnomo, Budi Supriatono; Nasim, Arim; Besar, Mohd. Hairul Azrin Haji; Suryadi, Edi (Islamic Research, 2024)
The purpose of this paper is to examine whether Mudharabah and Musyarakah financing from Islamic banks in Indonesia is capital or debt financing, based on legal, accounting, and fiqh perspectives. To achieve this goal, a review is carried out on laws, Sharia Accounting Standards, MUI and DSN Fatwas, the Al Quran and Hadith, articles, the Financial Reports of Islamic Banks in Indonesia, and other relevant documents. This study concludes that the law as stipulated in Act No. 21 of 2008 limits Islamic banking operational activities only to the financial sector, and it is almost impossible to implement in a real economy. The current provision does not allow Islamic banking to act as an investor in a mudharabah contract or as an asset owner in a musyarakah contract. This is confirmed in the financial reports of Islamic banks, which do not report mudharabah financing and musyarakah financing as investments. In addition, in practice, Contract musyarakah cannot stand on its own but must be carried out in a multi-contract (hybrid) manner. Even though the Prophet had forbidden the practice of two contracts in one transaction. On the other hand, in distributing financing, banks do not have a sharia contract basis to act as shaibul mal. The bank's status as Al-Wakil or Mudharib does not justify it changing its status to Shahibul Mal when disbursing funds. As a result, the Contract of mudharabah and musyarakah financing carried out by banks with customers as mudharib becomes void.